Efficacy of platelet-rich fibrin application for improving collagen density of gingival connective tissue in periodontitis-induced rabbits - Nasution, Aini Hariyani; Dewanti, Wenny (Padjadjaran Journal of Dentistry, 2022)
Introduction: Due to the high prevalence of periodontal diseases that increase the possibility of tooth loss, platelet-rich fibrin (PRF) as a regenerative treatment has been proposed. PRF is a potential second-generation platelet concentrate and autologous healing biomaterial which contain growth factors that accelerate wound healing mechanisms. This study aimed to evaluate the efficacy of platelet-rich fibrin application to improve gingival connective tissue collagen density in periodontitis-induced rabbits. Methods: An experimental study with a post-test only control group design approach was conducted on 20 samples calculated using the Federer formula. Periodontitis was induced in ten rabbits with silk ligatures tied around the cervical region of central incisors teeth bilaterally for 14 days. After periodontitis occurred, phase I treatment was performed and followed by curettage. PRF was placed in the lower region as a treatment group using a split-mouth design, whereas a control group without PRF was in the upper jaw region. Subjects were euthanised after the 7th and 14th days of healing. Histopathological analysis was performed, and collagen density was quantified using ImageJ software. Statistical analysis was carried out using paired-T and two-way ANOVA tests. Results: There was a significant difference (p=0.001; p<0.05) in gingival connective tissue collagen density between treatment and control groups on the 7th and 14th days of observation. There was a significant increase in gingival connective tissue collagen density in the treatment group. Conclusion: Platelet-rich fibrin could improve gingival connective tissue collagen density in periodontitis-induced rabbits.